2012
DOI: 10.1590/s0073-47212012000200004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of prior experience with artificial fruits on the ovipositioning behavior of Anastrepha fraterculus (Diptera, Tephritidae)

Abstract: ABSTRACT. The South American fruit fly, Anastrepha fraterculus (Wiedemann, 1830) (Diptera, Tephritidae), is a leading pest of Brazilian fruit crops. This study evaluated how prior experience with artificial fruits containing peach and/or guabiroba pulp influenced the ovipositing behavior of A. fraterculus. Insects 15-21 days old were exposed to four treatments: 1) experience with guabiroba, Campomanesia xanthocarpa O. Berg (Myrtaceae); 2) experience with peach, Prunus persica (L.) Batsch (Chimarrita cultivar; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Malo et al (2005) exposed A. ludens fruit flies to fruit volatiles and yellow spheres in a wind tunnel, to compare the behavioural responses of those insects, observing that both males and females were significantly more attracted to fruit volatiles than to unscented spheres. Gregorio et al (2012) reported finding more A. fraterculus eggs in substrates containing guabiroba ( Campomanesia xanthocarpa ) and peach pulp than in control substrates. Those authors attributed that preference to greater chemical compatibility between those substrates and the insects, with the larger numbers of eggs presumably reflecting the more adequate nutritional quality of the substrates for immature development.…”
Section: Discussionmentioning
confidence: 99%
“…Malo et al (2005) exposed A. ludens fruit flies to fruit volatiles and yellow spheres in a wind tunnel, to compare the behavioural responses of those insects, observing that both males and females were significantly more attracted to fruit volatiles than to unscented spheres. Gregorio et al (2012) reported finding more A. fraterculus eggs in substrates containing guabiroba ( Campomanesia xanthocarpa ) and peach pulp than in control substrates. Those authors attributed that preference to greater chemical compatibility between those substrates and the insects, with the larger numbers of eggs presumably reflecting the more adequate nutritional quality of the substrates for immature development.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors drive oviposition in insects: availability of food ( Stahlschmidt et al, 2014 ), assessment of threat from conspecifics ( Shelly, 1999 ; Ekesi et al, 2009 ), natural predators ( Van Mele et al, 2009 ), and most importantly, ovipositional stimulation and cues from the host ( Freeman and Carey, 1990 ; Kamala Jayanthi et al, 2012 , 2014a , b ). Insects carry the memory of ovipositional stimulant cues that are a part of the host volatiles which support their progeny survival ( Gregório et al, 2012 ; Kamala Jayanthi et al, 2014a ). A gravid female insect chooses the best possible oviposition sites to provide an environment suitable for the proper development of its progeny ( Fontellas-Brandalha and Zucoloto, 2004 ; Rattanapun et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained with A. fraterculus, in which exposure to guabiroba-based [Campomanesia xanthocarpa O. Berg. (Myrtaceae)] or peach-based [Prunus persica (L.) Batsch (Rosaceae)] artificial fruits influenced female selection (Greg orio et al, 2012).…”
Section: Introductionmentioning
confidence: 99%